Risk of major myopia-associated non-communicable ocular health disorders in Ghana. - Samuel Kyei; Rexford Kwasi Gyaami; John Baptist Abowine; Ebenezer Zaabaar; Kofi Asiedu; Samuel Bert Boadi-Kusi; Jacob Mensah Mesuh; Frank Assiamah; Anthony Armah; Patience Ansomah Ayerakwah (PLoS ONE, 2024)
Objective To assess the differential association of myopia with major non-communicable ocular diseases in an African clinical cohort. Methods A five-year hospital-based retrospective study of myopia cases. Patients' folders, Optical Coherence Tomography scans, and fundus photographs were reviewed for the abstraction of relevant data. Only records that employed recognized standards and classification systems for diagnosing and staging the various ocular conditions were included. Demographic characteristics, non-cycloplegic objective refractive findings, and non-communicable eye diseases were retrieved from the records. Myopia-associated risk factors were then determined using logistic regression and correlation. Results Some 16018 patients (32027 eyes) met the inclusion criteria for at least one eye comprising 50.8% males (n = 8137) and 49.2% females (n = 7881). The mean age of the patients was 43.14 ± 17.88 years (range: 2-98 years). The mean spherical equivalent± Standard deviation for myopia was -2.30±3.23 DS (range: -0.50 to -25DS). Binary logistic regression analysis showed that myopic eyes had a higher odd of AC (OR, 0.53; 95% CI, 0.50-0.57), POAG (OR, 6.0; 95% CI, 5.26-6.82), DR (OR, 10.70; 95% CI, 3.91-29.27) and cataracts (OR, 20; 95% CI, 15.32-26.20) but not dry eye (OR, 0.74, 95% CI, 0.68-0.81), macular degeneration and pterygium (OR, 0.36; 95% CI, 0.32-0.40). Conclusion Africans with myopia are more at risk of developing allergic conjunctivitis, cataracts, POAG, and DR but not for dry eye, macular degeneration, and pterygium.